The optical resolution of albuterol - Stevens, Anne Theresa (Department of Chemistry, 2016)
The acetonide derivative of (rac)-albuterol has been prepared and used as a substrate in cocrystallisation experiments with several acidic resolving agents~ Successful resolution of the acetonide was achieved with both di-0-benzoyl- and di-0-toluoyltartaric acid, with the (2S,3S)enantiomer of the acid selectively co-crystallising with the desired (R)-albuterol acetonide. High performance liquid chromatography on a chiral stationary phase, and 1H NMR experiments using a chiral shift reagent were used to assess the optical purity of the resolved material. Acid hydrolysis of the resolved acetonide gave rise to the target, (R)-albuterol, which was isolated as an acetate salt. The inferred absolute configuration of the resolved acetonide was assessed by 1H NMR analysis of its (R)-Mosher ester, and confirmed by an X-ray structural determination of its (R)-phenylethylurea derivative. The acetonide derivative of (rac)-albuterol has been prepared and used as a substrate in cocrystallisation experiments with several acidic resolving agents~ Successful resolution of the acetonide was achieved with both di-0-benzoyl- and di-0-toluoyltartaric acid, with the (2S,3S)enantiomer of the acid selectively co-crystallising with the desired (R)-albuterol acetonide. High performance liquid chromatography on a chiral stationary phase, and 1H NMR experiments using a chiral shift reagent were used to assess the optical purity of the resolved material. Acid hydrolysis of the resolved acetonide gave rise to the target, (R)-albuterol, which was isolated as an acetate salt. The inferred absolute configuration of the resolved acetonide was assessed by 1H NMR analysis of its (R)-Mosher ester, and confirmed by an X-ray structural determination of its (R)-phenylethylurea derivative.